2020
DOI: 10.3390/molecules25173875
|View full text |Cite
|
Sign up to set email alerts
|

Ethanolic Extract of Salvia hispanica L. Regulates Blood Pressure by Modulating the Expression of Genes Involved in BP-Regulatory Pathways

Abstract: Hypertension (HT) is considered to be a potential risk factor for cardiovascular diseases and has been directly related to pathologies such as obesity and dyslipidemias. Angiotensin-converting enzyme inhibitors (ACEIs) blocked the renin-angiotensin-aldosterone cascade diminishing the production of angiotensin II and the level of bradykinin, produced by the kallikrein-kinin system. Although ACEIs are effective therapeutics in regulating HT, they present several side-effects that can be due to their mechanism of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 46 publications
0
5
0
Order By: Relevance
“…Also, caffeic acid has been reported to inhibit ACE activity. 52 Compounds with antioxidant activity such as p -coumaric acid, benzoic acid, vanillic acid, and caffeic acid may possibly increase the expression of eNOS. 53 Similarly, the observed overexpression of COX-2 and NF-kB in the heart tissue might be responsible for the production of reactive oxygen species in the hypertensive rats.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Also, caffeic acid has been reported to inhibit ACE activity. 52 Compounds with antioxidant activity such as p -coumaric acid, benzoic acid, vanillic acid, and caffeic acid may possibly increase the expression of eNOS. 53 Similarly, the observed overexpression of COX-2 and NF-kB in the heart tissue might be responsible for the production of reactive oxygen species in the hypertensive rats.…”
Section: Discussionmentioning
confidence: 99%
“…bracteosa contains compounds such as caffeic acid and quercetin possessing effective antioxidant activity supports this hypothesis. Also, caffeic acid has been reported to inhibit ACE activity . Compounds with antioxidant activity such as p -coumaric acid, benzoic acid, vanillic acid, and caffeic acid may possibly increase the expression of eNOS .…”
Section: Discussionmentioning
confidence: 99%
“…Ullah et al (2016) reported a high intake of αlinolenic acid by humans reduces the risk of heart failure. This may be due to the anti-inflammatory, anti-thrombotic and anti-arrhythmic role that chia seeds, as a natural source of omega 3 and 6 fatty acids, play (Oliveira-Alves et al, 2017;Arredondo-Mendoza et al, 2020). A study conducted by Koh et al (2015) showed that increased intake of Kulczyński et al (2019) omega 3 fatty acids from marine or plant sources by humans reduces the risk of cardiovascular diseases, which are among the most chronic noncommunicable diseases in the world is facing at present.…”
Section: Fat Composition Of Chia Seedsmentioning
confidence: 99%
“…Salvia hispanica seeds are rich in essential fatty acids (81%), including α‐linolenic acid (ALA, ω‐3, 62%) and linoleic acid (LA, ω‐6, 19%) with low ω‐6:ω‐3 ratio (0.3), which makes it one of the best sources of plant‐based ω‐3 (Oteri et al., 2023). Several studies examining the effect of ω‐3 polyunsaturated fatty acids (ω‐3‐PUFAs) supplementation on human health suggest that they may help reduce several chronic diseases such as diabetes, cardiovascular and inflammatory disorders, hypertension, dyslipidemia, and kidney dysfunction (Arredondo‐Mendoza et al., 2020; Creus et al., 2017; El‐Feky et al., 2022; Y.‐X. Liu et al., 2023; Meyer & De Groot, 2017; Ong et al., 2023; Onneken, 2018; Penson & Banach, 2020; Y. Xiao et al., 2022; X. Zhang et al., 2022).…”
Section: Introductionmentioning
confidence: 99%